2008
DOI: 10.1073/pnas.0808606105
|View full text |Cite
|
Sign up to set email alerts
|

A functional nitric oxide reductase model

Abstract: A functional heme/nonheme nitric oxide reductase (NOR) model is presented. The fully reduced diiron compound reacts with two equivalents of NO leading to the formation of one equivalent of N 2O and the bis-ferric product. NO binds to both heme Fe and nonheme Fe complexes forming individual ferrous nitrosyl species. The mixed-valence species with an oxidized heme and a reduced nonheme Fe B does not show NO reduction activity. These results are consistent with a so-called ''trans'' mechanism for the reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
104
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 43 publications
7
104
0
2
Order By: Relevance
“…Nitric oxide reductase is the primary enzyme in a chain of catalytic reactions leading to the production of N 2 O (Hino et al, 2010;Hendriks et al, 2000). The catalytic cycle involving production of N 2 O from NO has yet to be completely understood with respect to the formation of the N-N double bond, the complexity of the structural information of nitric oxide reductase, the proton transfer pathway into nitric oxide reductase (Tosha and Shiro, 2013), and the very short lifetime of the intermediate states of the molecules (Collman et al, 2008). We hypothesized that the difference in the bulk observed during incubation of our two bacterial species was due to different nitric oxide reductases produced by the two species.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide reductase is the primary enzyme in a chain of catalytic reactions leading to the production of N 2 O (Hino et al, 2010;Hendriks et al, 2000). The catalytic cycle involving production of N 2 O from NO has yet to be completely understood with respect to the formation of the N-N double bond, the complexity of the structural information of nitric oxide reductase, the proton transfer pathway into nitric oxide reductase (Tosha and Shiro, 2013), and the very short lifetime of the intermediate states of the molecules (Collman et al, 2008). We hypothesized that the difference in the bulk observed during incubation of our two bacterial species was due to different nitric oxide reductases produced by the two species.…”
Section: Discussionmentioning
confidence: 99%
“…In biological systems, this reaction is performed by NO reductase (NOR) and flavodiiron NO reductase (FDP), [1][2][3][4][5][6][7][8][9][10][11][12] which convert two equivalents of nitric oxide, two reducing equivalents, and two protons, into N 2 O and water. The exact order of proton and electron additions during their catalytic cycles is not known, nor is the mechanism by which the N-N bond of N 2 O is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies of these synthetic models have offered many insights. For example, Collman et al showed that a fully reduced heme/nonheme Fe B compound can react with two equivalents of NO leading to the formation of one equivalent of N 2 O and a bis-ferric product (41). On the other hand, Karlin and coworkers showed that a small heme/Cu complex can efficiently lead to reductive coupling of NO to N 2 O (43).…”
mentioning
confidence: 99%
“…Despite these successes, the roles of the conserved glutamates and metal ions still remain to be fully elucidated, partly because of the difficulty in obtaining native NOR in high yield and the lack of a 3D structure. Even if these problems are resolved, it is still difficult to replace iron in the native Fe B site with other metal ions, and spectroscopic studies of native NOR are often complicated by the presence of other metal cofactors (e.g., low-spin heme).To overcome these limitations, a number of synthetic models of NOR using small organic molecules as ligands, have been made in which the nonheme Fe B site can be replaced by a copper ion (17,(38)(39)(40)(41)(42)(43)(44)(45). In addition, since these model systems lack additional metal-binding sites, spectroscopic studies are often simplified.…”
mentioning
confidence: 99%
See 1 more Smart Citation